Legal Action for Pre-Project Selling Based Buyers Whose Apartment Specification Have Changed Without Prior Approval - Atma Yuwita, Anggit (NORMA, 2020)
One of the alternatives that can be used as a residence is an apartment. This study aims to know and analyze how the apartment buyers' dispute settlement is experiencing changes in the apartment location without prior notification and approval. This is normative legal research that will explore the legislation's contents. Based on the study results, the sale and purchase of apartments done by ordering then made a Sale and Purchase Agreement (PPJB) that ensures the apartment will not be sold to others and delivered according to the time specified. Besides, it also regulated in Law Number 8 the Year 1999 concerning Consumer Protection and Law Number 20 the Year 2011 on Flats. Therefore, in case of misuse in the sale and purchase of an apartment, the consumer may initiate legal action based on the existing PPJB and Consumer Protection Law.Keywords: PPJB, Apartment, Consumer